METODE MURAJA’AH DALAM MENGHAFAL AL-QUR’AN SANTRI PROGRAM BAITUL QUR’AN (PBQ) DI PONDOK PESANTREN MODERN DINIYYAH PASIA - Rahmat Dani; Charles; Arifmiboy; Iswantir M (KOLONI, 2022)
This research is motivated by PBQ students who are less able to keep the memorization of the Qur'an so that many of them forget or lose their memorization, secondly, the lack of time for students to practice memorizing the Qur'an because of the full day class hours used in Islamic boarding schools, which third, some students do not understand the muraja'ah method in memorizing the Qur'an. So that researchers are interested in researching the muraja'ah method in memorizing the Qur'an of PBQ students ppm Diniyyah Pasia, to find out how the implementation of the muraja'ah method in memorizing the Qur'an of PBQ students at PPM Diniyyah Pasia. This research is a qualitative research. In collecting data using observation methods, in-depth interviews and documentation, using data reduction analysis, data presentation and drawing conclusions. The results showed that the application of the muraja'ah method in memorizing the Al-Qur'an Baitul Qur'an program at Pondok Pesantren Diniyyah Pasia there were 5 implementations of muraja'ah memorizing the Qur'an, namely: 1) Muraja'ah memorizing individually and listened to by the ustadz, 2) Muraja'ah memorizing the Qur'an was done with friends, 3) Muraja'ah memorizing the old and new to the ustadz, 4) Muraja'ah memorizing together once a week, 5) rote test Al-Qur'an. The application of the muraja'ah method in the Baitul Qur'an Program in memorizing the Qur'an, students have been able to achieve the memorization target that has been programmed at PBQ, students are able to memorize the Qur'an properly, correctly according to their makhraj and tajwid. The students' memorization after the application of the muraja'ah method became more fluent, fluent and tartil. With the muraja'ah method, students are able to speed up their memorization compared to not muraja'ah, besides that, students' memorization becomes stronger, both old memorization or new memorization.  Keywords: Muraja'ah Method, Memorizing the Qur'an, PBQ Santri at PPM Diniyyah Pasia